Reconstruction of the Business Model Canvas Based on Customer Journey to Enhance FourG Villa's Revenue in Bandung's Hospitality Industry - Gina Aninditha; Ilma Aulia Zaim; Satya Aditya Wibowo (Universitas Warmadewa, 2025)
This study integrates customer journey analysis with the Business Model Canvas (BMC) to enhance FourG Villa’s business model. Using a mixed-methods approach, key factors such as booking ease, facility quality, and staff responsiveness were identified as crucial for customer satisfaction and revisit intention. Recommendations include improving communication, facilities, and staff training to boost occupancy and customer loyalty.